2004
DOI: 10.1029/2002jc001614
|View full text |Cite
|
Sign up to set email alerts
|

Anticyclonic‐cyclonic eddies and their impact on near‐surface chlorophyll stocks and oxygen supersaturation over the Campeche Canyon, Gulf of Mexico

Abstract: Physical and biological data were gathered over the Campeche Canyon area, Gulf of Mexico, in summer 1999. These include hydrographical and meteorological parameters, and oxygen content, as well as, at some oceanographic stations, suspended particulate matter (SPM), chlorophyll‐a, and in vivo natural fluorescence profiles. Dry air from the east set up a latent heat flux that ranged from 50 to 300 Wm−2. The wind mixed layer (ML) was isothermal and averaged 40 m thick, but with a noticeable increase of oxygen sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 28 publications
2
21
0
3
Order By: Relevance
“…Since k-values varies according to the wavelengths of light, values ranging from 0.035 to 0.140 m -1 have been reported by Lalli & Parsons (2006), in agreement with our observations. Similar observations were reported by Salas de León et al (2004) who found mean values of k of 0.05 for waters of the southern Gulf of Mexico. According to Falwowski & Raven (2007), values of k could be potentially affected by the amount of chlorophyll contained in living phytoplankton and in plant debris or the dissolved and particulate matter along water column.…”
Section: Resultssupporting
confidence: 90%
“…Since k-values varies according to the wavelengths of light, values ranging from 0.035 to 0.140 m -1 have been reported by Lalli & Parsons (2006), in agreement with our observations. Similar observations were reported by Salas de León et al (2004) who found mean values of k of 0.05 for waters of the southern Gulf of Mexico. According to Falwowski & Raven (2007), values of k could be potentially affected by the amount of chlorophyll contained in living phytoplankton and in plant debris or the dissolved and particulate matter along water column.…”
Section: Resultssupporting
confidence: 90%
“…The velocity patches of the instantaneous velocities (contours of −45 cm s −1 in Figures 6a and 6c) on the leeward side of the hollow could have represented internal motions [ Benjamin and Seaman , 1985; Armi , 1986; Davis , 1997]. These motions could have been produced by the interaction between the increasing bottom slope and the stratified flow [ Salas‐de‐León et al , 2004] but were not resolved appropriately by the sampling. The development of lee waves was better suggested by data from the anchored ADCP station.…”
Section: Resultsmentioning
confidence: 99%
“…The continental shelf extension is variable, which is very narrow off the coasts of TM and VR, progressively widening by the Yucatan Peninsula. Among the most important physiographic features of the GoM is the Campeche canyon that strongly influences oceanographic dynamics on a regional scale through the formation of eddies and upwelling events (Escobar‐Briones, Estrada‐Santillán, & Legendre, ; Salas‐de León, Monreal‐Gómez, Signoret, & Aldeco, ). The GoM oceanographic characteristics are largely determined by the presence of the Loop Current (Figure ), which is the dominant feature of the circulation in the eastern part of the GoM and shows great seasonal and annual variability in trajectory and intensity (Aguirre, ; Monreal‐Gómez, Salas de León, & Gracia‐Gasca, ; Monreal‐Gómez, Salas de León, & Velasco‐Mendoza, ; Zavala‐Hidalgo, Morey, & O'Brien, ).…”
Section: Methodsmentioning
confidence: 99%